The Management of Left Pulmonary Artery Sling in Senegal: Our Experience from One Case (Cardiovascular Journal, 2017)
Pulmonary Artery Sling (PAS) is a rare congenital heart disease due to abnormal origin of Left Pulmonary Artery (LPA) from the Right Pulmonary Artery (RPA), then encircling the distal part of the trachea. The treatment is a surgical repair consisting of reimplantation of the LPA on the main pulmonary artery over cardiopulmonary bypass. The authors report a clinical case of PAS in a 5.5 years old boy diagnosed in Senegal then successfully operated in France.Cardiovasc. j. 2017; 10(1): 94-96